Prevalence of psychological distress: a scientific approach towards the mental health and wellbeing of population during the SARS-COV-2 outbreak [version 2; peer review: 2 approved, 1 approved with reservations] - Shazia Sadaf; Sara Noreen; Ahmed Alsubaie; Inayat Shah; Saman Tauqir; Saqib Ali (F1000Research)
Background The global challenge of the novel coronavirus has led to an unprecedented downturn, adversely affecting the health and mental wellbeing of communities worldwide. The objective of this study is to assess mental health and psychological distress levels within the general population of Peshawar, Pakistan amidst the ongoing COVID-19 pandemic. Method A cross-sectional online survey was conducted among 715 residents of Peshawar, Pakistan. The questionnaire collected data on demographics, socioeconomic status, and residential area. The Modified K10 Kessler Psychological Distress Scale was used to measure mental well-being. Descriptive statistics, including means and standard deviations, were calculated, and statistical analyses were performed using SPSS (IBM, USA, version 22). Results A total of 715 responses were collected. The comprehensive psychological distress score was identified as 25.55, signifying moderate stress levels. Among the respondents, 53.3% were females, 46.7% had completed a bachelor’s degree, 41% were employed, 78.7% were single, 93.1% were non-smokers, and 69.4% resided in urban areas. The study revealed that both gender (p=0.001) employment status (p=0.018) were linked to a more pronounced psychological impact of the outbreak. Conclusions This study highlights age, gender, employment status, and urbanization as influential factors contributing to psychological distress during the COVID-19 outbreak. As we face the challenges of the new normal, it is essential for policymakers to address these mental health concerns through targeted support and interventions, ensuring that mental health resources are accessible and responsive to the needs of affected populations.